Effect of Compression Garments on the Development of Edema and Soreness in Delayed-Onset Muscle Soreness (DOMS) - Heiss, Rafael (J Sports Sci Med, 2018)
Delayed-onset muscle soreness (DOMS), an ultrastructural muscle injury, is one of the most common reasons for impaired muscle performance. The purpose of this study was to investigate the influence of sport compression garments on the development of exercise-induced intramuscular edema in the context of DOMS. DOMS was induced in 15 healthy participants. The participants performed a standardized eccentric exercise of the calf muscles. Magnetic resonance imaging (MRI) was performed at baseline and 60h after exercise (T2-weighted signal intensity and T2 relaxation time was evaluated in each compartment and the intramuscular edema in the medial head of the gastrocnemius muscle was segmented). After the exercise, a conventional compression garment (18-21 mmHg) was placed on one randomized calf for 60h. The level of muscle soreness was evaluated using a visual analogue pain scale. T2-weighted signal intensity, T2 relaxation time and intramuscular edema showed a significant interaction for time with increased signal intensities/intramuscular edema in the medial head of the gastrocnemius muscle at follow-up compared to baseline. No significant main effect for compression or interaction between time and limb occurred. Further, no significant differences in the soleus muscle and the lateral head of the gastrocnemius muscle were noted between limbs or over time. After exercise, there was significantly increased muscle soreness in both lower legs in resting condition and when going downstairs and a decreased range of motion in the ankle joint. No significant difference was observed between the compressed and the non-compressed calf. Our results indicate that wearing conventional compression garments after DOMS has been induced has no significant effect on the development of muscle edema, muscle soreness, range of motion and calf circumference.